Erythrocyte zinc level in patients with atopic dermatitis and its relation to SCORAD index - Karabacak, Ercan; Aydin, Ersin; Kutlu, Ali; Ozcan, Omer; Muftuoglu, Tuba; Gunes, Ali; Dogan, Bilal; Ozturk, Sami (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : Atopic dermatitis (AD) is a chronic, pruritic inflammatory disease, characterized by a relapsing-remitting course. The pathogenesis of atopic dermatitis is not completely understood, although the disorder appears to result from the complex interaction between immune abnormalities, genetic and environmental factors. Trace elements are essential for normal functioning of the immune system. Aim :To determine zinc levels in serum and erythrocytes of patients with AD using an atomic absorption spectrometric technique and to investigate the relationship between those levels and disease activity. Material and methods : Sixty-seven patients and 49 controls were enrolled into the study. The disease severity of AD patients was determined according to the Scoring Atopic Dermatitis (SCORAD) index. We measured zinc levels in serum and erythrocytes by the atomic absorption spectrophotometric technique. Results : Erythrocyte zinc levels were significantly lower in AD patients than in the control group (p < 0.001), whereas serum zinc levels did not differ between the groups (p = 0.148). In the AD patient group there was a negative correlation between the SCORAD score and erythrocyte zinc levels (r = –0.791; p < 0.001). Conclusions : The negative relationship between disease severity and erythrocyte zinc levels might suggest an immunopathological link between AD progression and intracellular zinc metabolism.